2021
DOI: 10.1038/s42003-021-02114-0
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant activity of mitochondrial NCLX is linked to impaired synaptic transmission and is associated with mental retardation

Abstract: Calcium dynamics control synaptic transmission. Calcium triggers synaptic vesicle fusion, determines release probability, modulates vesicle recycling, participates in long-term plasticity and regulates cellular metabolism. Mitochondria, the main source of cellular energy, serve as calcium signaling hubs. Mitochondrial calcium transients are primarily determined by the balance between calcium influx, mediated by the mitochondrial calcium uniporter (MCU), and calcium efflux through the sodium/lithium/calcium exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 112 publications
(120 reference statements)
6
32
0
Order By: Relevance
“…The identification of diverse mitochondrial and ion channel proteins as susceptibility biomarkers for the development of schizophrenia in both genome‐wide association study (GWAS) and whole exome protein‐coding sequence studies 9,15,17,18 is in agreement with our findings of abnormal NDEV levels of NCLX, LETM1, and CACNA‐1C, in FP (Figure 2). CACNA‐1C is a voltage‐regulated calcium channel that regulates mitochondrial bioenergetics at several levels.…”
Section: Discussionsupporting
confidence: 88%
“…The identification of diverse mitochondrial and ion channel proteins as susceptibility biomarkers for the development of schizophrenia in both genome‐wide association study (GWAS) and whole exome protein‐coding sequence studies 9,15,17,18 is in agreement with our findings of abnormal NDEV levels of NCLX, LETM1, and CACNA‐1C, in FP (Figure 2). CACNA‐1C is a voltage‐regulated calcium channel that regulates mitochondrial bioenergetics at several levels.…”
Section: Discussionsupporting
confidence: 88%
“…As attempts to validate NCLX knockdown on the protein level using several commercially available antibodies yielded variable results—consistent with a number of recent studies citing the inadequacy of most anti-NCLX antibodies to detect native NCLX protein ( 28 , 29 , 30 )—we verified the effectiveness of our shRNAs for reducing NCLX protein expression by cotransfecting human embryonic kidney 293 (HEK293) cells with a plasmid driving the coexpression of enhanced GFP (EGFP) and murine NCLX (pAAV-EGFP.T2A.NCLX; Fig. S2 A ) and plasmids driving the expression of shCTRL, shNCLX, shNCLX-2, or none of these ( Fig.…”
Section: Resultssupporting
confidence: 52%
“…The difference in excitability might reflect altered synaptic activity in KO neurons. A recent study showed that the deletion of NCLX caused decreased synaptic activity and plasticity in neuronal mitochondria ( 58 ). When we included in our analysis only those neurons that were responsive to Bicu + 4AP, we found that Δ[Ca 2+ ] c rise was not significantly attenuated in KO as compared with WT neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%